Rural radio goes to town - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
That old favourite of thousands of rural radio stations, the Developing Countries Farming Radio Network, recently expanded its coverage to urban agriculture and animal breeding. Now the DCFRN programmes scripts, made available free of charge to...